THE INFLUENCE OF WORK EXPERIENCE ON EMPLOYEE PERFORMANCE AT THE EDUCATION AND CULTURE OFFICE OF SIDENRENG RAPPANG REGENCY - Aswandi, Aswandi; Amin, Gazali; Ayu, Ari (Universitas Ichsan Sidenreng Rappang, 2025)
Based on observations conducted by the researcher on employees at the Department of Education and Culture Office in Sidenreng Rappang Regency, further examination is needed. There are still employees who lack work experience relevant to the tasks assigned by their superiors, including employees with less than one year of service. This poses a challenge to improving employee performance and has led to a decline in performance within the Department of Education and Culture Office in Sidenreng Rappang Regency. The objective of this research is to determine whether work experience significantly influences employee performance at the Department of Education and Culture in Sidenreng Rappang Regency. A quantitative research method was used. The research population consisted of 85 employees at the Department of Education and Culture in Sidenreng Rappang Regency. Using probability sampling or random sampling techniques and the Slovin formula, the sample size was determined to be 46 employees. Each member of the population (employees) had an equal chance of being selected as a sample, with the selection process being random without considering the strata within the population. The analysis results indicate that work experience has a significant effect on employee performance, with a calculated t-value (3.297) greater than the t-table value (2.015). Therefore, the hypothesis stating that work experience influences employee performance is accepted. The coefficient of determination (R Square) value of 0.198 indicates that approximately 19.8% of the variance in the dependent variable (Y) employee performance is influenced by the independent variable (X) work experience. The remaining 80.2% is attributed to other variables not examined in this research.